Socioeconomic disparities in childhood cancer survival in Switzerland. Issue 12 (1st March 2016) - Adam, Martin; Rueegg, Corina S.; Schmidlin, Kurt; Spoerri, Adrian; Niggli, Felix; Grotzer, Michael; von der Weid, Nicolas X.; Egger, Matthias; Probst‐Hensch, Nicole; Zwahlen, Marcel; Kuehni, Claudia E.; ,
Abstract : In this study, we investigated whether childhood cancer survival in Switzerland is influenced by socioeconomic status (SES), and if disparities vary by type of cancer and definition of SES (parental education, living condition, area‐based SES). Using Cox proportional hazards models, we analyzed 5‐year cumulative mortality in all patients registered in the Swiss Childhood Cancer Registry diagnosed 1991–2006 below 16 years. Information on SES was extracted from the Swiss census by probabilistic record linkage. The study included 1602 children (33% with leukemia, 20% with lymphoma, 22% with central nervous system (CNS) tumors); with an overall 5‐year survival of 77% (95%CI 75–79%). Higher SES, particularly parents' education, was associated with a lower 5‐year cumulative mortality. Results varied by type of cancer with no association for leukemia and particularly strong effects for CNS tumor patients, where mortality hazard ratios for the different SES indicators, comparing the highest with the lowest group, ranged from 0.48 (95%CI: 0.28–0.81) to 0.71 (95%CI: 0.44–1.15). We conclude that even in Switzerland with a high quality health care system and mandatory health insurance, socioeconomic differences in childhood cancer survival persist. Factors causing these survival differences have to be further explored, to facilitate universal access to optimal treatment and finally eliminate social inequalities in childhood cancer survival. Abstract : What's new? Socioeconomic status (SES) is a significant factor in access to health care but its influence on cancer survival in high‐income countries with mandatory health insurance is unclear. Here the authors investigate the influence of SES on childhood cancer survival in Switzerland. They report a striking socioeconomic gap in survival of pediatric CNS tumor, but not leukemia, patients. This result points to a lack of therapy standardization in the treatment of pediatric CNS tumors, underscoring the need for universal access to optimal cancer treatment for all patients even in an affluent country like Switzerland.